Plasma physics and engineering - Fridman, Alexander A., 1953-.; Kennedy, Lawrence A., 1937-. (Boca Raton, FL : CRC Press, 2011)
"Plasma engineering is a rapidly expanding area of science and technology with increasing numbers of engineers using plasma processes over a wide range of applications. An essential tool for understanding this dynamic field, Plasma Physics and Engineering provides a clear, fundamental introduction to virtually all aspects of modern plasma science and technology, including plasma chemistry and engineering, combustion, chemical physics, lasers, electronics, methods of material treatment, fuel conversion, and environmental control. The book contains an extensive database on plasma kinetics and thermodynamics, many helpful numerical formulas for practical calculations, and an array of problems and concept questions"--Provided by publisher.
Keywords: Plasma (Ionized gases).; Plasma engineering